ChemInform Abstract: Dialkylimidazolium Dimethyl Phosphates as Solvents and Catalysts for the Knoevenagel Condensation Reaction. Issue 33 (19th August 2014) - Zicmanis, Andris; Anteina, Liene
Abstract Knoevenagel condensation between benzaldehyde and ethyl cyanoacetate in the presence of an equimolar amount of 1, 3‐dialkylimidazolium dimethyl phosphate ionic liquids is investigated.